2013
DOI: 10.1093/nar/gkt1182
|View full text |Cite
|
Sign up to set email alerts
|

canSAR: updated cancer research and drug discovery knowledgebase

Abstract: canSAR (http://cansar.icr.ac.uk) is a public integrative cancer-focused knowledgebase for the support of cancer translational research and drug discovery. Through the integration of biological, pharmacological, chemical, structural biology and protein network data, it provides a single information portal to answer complex multidisciplinary questions including—among many others—what is known about a protein, in which cancers is it expressed or mutated, and what chemical tools and cell line models can be used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 16 publications
(22 reference statements)
2
75
0
Order By: Relevance
“…Primer pairs with comparable efficiency of amplification were identified and efficiency was assessed using serial dilutions of cDNA (20) prepared from OAW28 ovarian carcinoma cells that contain wild type FGFR3 and TACC3 (21). Primers used are: N-terminal region of FGFR3, FGFR3-N: Forward 5′-AAGACGATGCCACTGACAAG-3′, Reverse 5′-CCCAGCAGGTTGATGATGTTTTTG-3′; C-terminal region of TACC3, TACC3-C: Forward 5′-TCCTTCTCCGACCTCTTCAAGC-3′, Reverse 5′-TAATCCTCCACGCACTTCTTCAG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…Primer pairs with comparable efficiency of amplification were identified and efficiency was assessed using serial dilutions of cDNA (20) prepared from OAW28 ovarian carcinoma cells that contain wild type FGFR3 and TACC3 (21). Primers used are: N-terminal region of FGFR3, FGFR3-N: Forward 5′-AAGACGATGCCACTGACAAG-3′, Reverse 5′-CCCAGCAGGTTGATGATGTTTTTG-3′; C-terminal region of TACC3, TACC3-C: Forward 5′-TCCTTCTCCGACCTCTTCAAGC-3′, Reverse 5′-TAATCCTCCACGCACTTCTTCAG-3′.…”
Section: Methodsmentioning
confidence: 99%
“…In colorectal adenocarcinoma the Colon Cancer Atlas Network (33) revealed 5.56% UBE2M mutant tumors, but the function of those mutations remain unclear. Two studies found elevated expression of UBE2M in colon adenocarcinoma when compared to normal tissue (34), but again, relevance with regard to treatment efficacy is unclear. Furthermore, no knockout mouse model has been described so far.…”
Section: Discussionmentioning
confidence: 99%
“…The protein annotation and chemoinformatics analysis of the ZIKV-related genes was performed using the canSAR 2.0 integrated knowledgebase, a publically available database [37]. The Browse canSAR analysis tool was used and the ZIKV-associated proteins were batch analyzed for protein annotations, 3D structures, compounds and bioactivity-related information.…”
Section: Methodsmentioning
confidence: 99%
“…A recently described database of ZIKV related genes [35,36] were subjected to chemoinformatics analysis using the canSAR integrated protein annotation tool [37]. Using ligand-based druggability analysis scores, RO5 compliant active hit compounds (IC 50 < 100nM) for 35 ZIKV targets were identified.…”
Section: Introductionmentioning
confidence: 99%